OS2.2 Chemotherapy for spinal gliomas in adults. (6th September 2019) - Gramatzki, D; Felsberg, J; Bähr, O; Hentschel, B; Westphal, M; Schackert, G; Tonn, J C; Herrlinger, U; Löffler, M; Pietsch, T; Steinbach, J; Reifenberger, G; et al.
Abstract: BACKGROUND: Chemotherapy is a treatment option in patients diagnosed with anaplastic gliomas or glioblastomas of the spinal cord, or with recurrent lower graded WHO spinal gliomas that are no longer amenable to local treatment. The low incidence of spinal cord gliomas, particularly in adults, limits the ability to perform clinical trials. The role of chemotherapy in these tumors has remained unclear. MATERIAL AND METHODS: We performed a retrospective study of 22 patients diagnosed with spinal gliomas who were treated with chemotherapy at any time during the disease course. Benefit from chemotherapy was estimated by applying Response assessment in neuro-oncology criteria. Data on radiotherapy, as well as the number of neurosurgical interventions were taken into consideration. RESULTS: Most patients were diagnosed with astrocytoma WHO grade I-IV (N=14), the remaining patients were diagnosed with ependymoma (N=8). Median follow-up from start of chemotherapy was 92 months (95% CI, 72.6–111.4). The O 6 -methylguanyl-DNA-methyltransferase(MGMT)promoter methylation status was available in tumors of 12 patients: 9 tumors (75%) had an unmethylated MGMT promoter. More than 50% of the patients had more than one neurosurgical intervention. After prior surgery 10 patients in the first-line setting had chemotherapy combined with radiotherapy, while 3 patients received chemotherapy only. The remaining 9 patients had initially received radiation therapy and chemotherapy was given at time of recurrence. In patients diagnosed with astrocytoma mainly temozolomide (TMZ) was applied (N=10), while one patient received CCNU and three patients had combination chemotherapy. Patients diagnosed with ependymoma had hydroxyurea (N=1), CCNU (N=1), TMZ (N=3) or combination chemotherapy (N=3). In the group of patients who had chemotherapy combined with radiation, response rates were as follows: anaplastic astrocytoma 3 stable diseases (SD), glioblastoma 1 complete response (CR) and 1 SD, and anaplastic ependymoma 1 SD. After chemotherapy in the group of patients previously irradiated, the following response rates were observed: 1 SD in pilocytic astrocytoma, 1 SD in diffuse astrocytoma, 3 SD in myxopapillary ependymoma, and 2 SD and 1 partial response (PR) in anaplastic ependymoma. All other patients experienced progressive disease. There was no indication for a favorable prognostic role of MGMT promoter methylation. CONCLUSION: Spinal cord gliomas represent a heterogeneous group of tumors. Survival outcomes in response to chemotherapy in adult spinal glioma patients vary substantially, but individual patients appear to derive benefit from chemotherapy.